Foreign direct investment and economic growth: Evidence from Southern Asia - Mehdi Behname (Atlantic Review of Economics, 2012)
The aim of this paper is to investigate the influence of foreign direct investment (FDI) on economic growth in Southern Asia for the period 1977-2009. The Im, Pesaran and Shin (2003) unit root test shows the variables are stationary in level and Hausman (1978) test proves that we should apply the random effects model. Having estimated the model we come to the conclusion that foreign direct investment (FDI) has positive and significant effect on economic growth and variables such as human capital, economic infrastructure and capital formation have positive effect on gross domestic product (GDP). But, population, technology gap and inflation have negative effect on the economic growth.
Keywords: F21; F43; 330; Direct Investment; Economic Growth; Southern Asia; Panel Data